LECTIN RECEPTORS IN RAT LUNGS AT NORMAL CON-DITION AND IN EXPERIMENTAL HYPOTHYROIDISM - Pankevych, L.; Yashchenko, A.; Nakonechna, O.; Chelpanova, I. (World of Medicine and Biology, 2012)
Glycoconjugates of the lungs structures were studied using lectin-peroxidase method. Horseradish peroxidase-labeled lectine set included such lectines, as concanavalin A (ConA, αDMan specific), Arachis hypogea (PNA specific for a βDGal(β1-3)DGalNAc), Glycine max(SBA, specific for a DGalNAc), Helix Pomatia (HPA, specific for αDGalNAc), Triticum vulgaris (WGA, specific for DGlcNAc, NeuNAc), Sambucus Nigra (SNA, specific for Neu5Ac(α2-6)Gal/DGalNAc), Laburnum anagyroides (LABA, specific for αLFuc). It has been shown that experimental hypothyroidism is associated with moderate perivascular edema and lectin receptor modification in the lungs structures. This phenomenon stimulates the immune process activation that results in increased number of the SBA- positive alveolar macrophages and BALT-associated LABA positive dendritic cells.
Keywords: hypothyroidism; lectinhistchemistry; lungs; rat